Enhancing employee’s job satisfaction in Vietnam: Exploring the impact of organizational commitment, supervisor emotional support and training - Ngoc, Thuy Doan Thi; Huu, Hao Nguyen; Minh, Tuan Phan; Lam, Thinh Do Huynh; Van, Dung Nguyen (Journal of Social Economics Research, 2024)
Job satisfaction is an important factor in promoting an employee’s well-being, productivity, and organizational success. Generally, when job satisfaction is high, employees experience greater emotions of fulfillment, motivation, and engagement. This can result in increased productivity, improved performance, and a decrease in employee turnover rates. Low job satisfaction, on the other hand, can result in tension, exhaustion, and a diminished sense of accomplishment and job security. It can also have negative effects on a person's physical and mental health and lead to decreased productivity, increased absenteeism, and increased turnover rates. Therefore, it is interesting to study some factors behind job satisfaction, especially in the context of a developing country. In particular, this study examines the roles of organizational commitment, supervisory emotional support, and training in job satisfaction. Furthermore, this research also investigates the moderating impact of training on the organizational commitment-job satisfaction relationship. The research collected data on office employees in Vietnam from December 2022 to January 2023. The quantitative analysis was conducted using SPSS and AMOS software. The findings reveal that organizational commitment, supervisory emotional support, and training have positive influences on job satisfaction. Additionally, training has a positive moderating role in the organizational commitment -job satisfaction nexus. The practical implications emphasize that organizations should create a supportive work environment and encourage emotional support from managers. Moreover, companies should prioritize training opportunities for staff members to improve their work satisfaction.